Branding a Memorable: Case Study on Residivist Streetwear Bandung - Safiratul Zakiyah; Yulianti Yulianti (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
The trust issue occurred toward the former prisoners made it difficult for them to return to society. Based on this issue, an effort was made to counter the stereotypes developed in the community. Unlike other clothing businesses, Residivist Streetwear has a unique concept, which manifested in the design of its products. Residivist Streetwear uses the idea of